Efeito preventivo dos triterpenos α, ß-amirina na doença hepática gordurosa não-alcoólica induzida por dieta em camundongos - Lima, Renan Pereira de (2019)
Non-alcoholic fatty liver disease (NAFLD) is a clinical-pathological condition defined by the abnormal accumulation of triglycerides in hepatocytes, commonly called hepatic steatosis (HS). Currently, only pioglitazone, an insulin sensitizing agent, and vitamin E as an antioxidant are recommended for the treatment of non-alcoholic hepatic steatosis by international guidelines. In the search for new therapeutic options for the treatment of NAFLD, triterpenic compounds isolated from medicinal plants are being investigated for their potential for the treatment of NAFLD. The present study investigated the effect of the mixture of α, β-amyrin (AMY) triterpenes isolated from Protium heptaphyllum in nonalcoholic fatty liver disease (NAFLD) induced by hyperlipidic diet (DH) in mice. The mice were divided into 5 groups and fed a standard diet (DP) or hyperlipidic diet (DH) and treated simultaneously with AMY (10 and 20 mg / kg) and fenofibrate (FEN) 50 mg/kg in drinking water for 15 weeks . Animals treated with AMY 10 and 20mg / kg and FEN 50mg / kg showed a significant reduction in body weight, abdominal fat, subcutaneous fat, subscapular weight, as well as liver weight and plasma levels of glucose, ALT, AST, cholesterol total, LDL, VLDL and triglycerides in relation to the DH group. AMY (10 and 20 mg / kg) and FEN (50 mg / kg) were able to significantly reduce hepatic lipid levels (total cholesterol and triglycerides) in relation to the DH group. Mice fed with DH presented a hyperglycemic pattern during the intraperitoneal glucose tolerance test (TTGI) and reduced insulin tolerance in the intraperitoneal insulin tolerance test (TTII), compared to the DP group. Triterpene was able to improve glucose and insulin tolerance in relation to the DH group. In addition to improving insulin resistance, AMY reduced the hepatic concentration of malondialdehyde and increased the hepatic concentration of reduced glutathione (GSH) compared to the DH group. AMY reduced the accumulation of neutral lipids in the liver evidenced by oil red O coloration when compared to the DH group. Treatment with AMY (10 and 20 mg / kg) and FEN (50 mg / kg) significantly reduced the expression of SREBP1 and FAS proteins and significantly increased the expression of PPARα and pAMPK proteins in the liver, concomitantly decreased gene expression ACC1, FAS and CD36 in hepatic tissue. AMY at concentrations of 3.1 – 400 μg / mL did not promote changes in cell viability of HepG2 cells in the MTT assay. In protocol of hepatic steatosis induced by oleic acid (AO), AMY at the concentrations of 12.5, 25 and 50 μg / mL reduced lipid accumulation when compared to the group that was induced only with AO, observed by oil red O staining. The results demonstrate potential hepatoprotective effect of AMY, listing it as a possible product for prevention of NALFD. The results suggest that the effect of triterpene is associated with the reduction of lipotoxicity and insulin resistance, thus preventing the progression of NAFLD.